2017
DOI: 10.1002/macp.201600562
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of Intramolecular and Intermolecular Hydrogen‐Bonding Systems on the Polymerization of Amide‐Containing Benzoxazines

Abstract: Pure para and ortho position amide benzoxazines, pHBA-a and oHBA-a, are synthesized. The hydrogen bonding interactions occurring in pHBA-a and oHBA-a are studied by Fourier transform infrared (FT-IR) spectroscopy and proton nuclear magnetic resonance ( 1 H NMR) spectroscopy. FT-IR results show that, while pHBA-a presents intermolecular hydrogen bonding interactions, oHBA-a exhibits an intramolecular five-membered-ring hydrogenbonding system between the NH in the amide group and the oxygen in the oxazine ring. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…Synthesis of PH‐a was carried out in a solvent‐less method following a modified reported procedure, as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of PH‐a was carried out in a solvent‐less method following a modified reported procedure, as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…Among these monomers, o HTI-a was the only one that has a crystal-to-crystal phase-transition [27,32]; hence, the unexpected low melting temperature of o HTI-a can be attributed to the formation of less stable crystalline structures. Besides, the thermograms showed that the maxima of the ring-opening polymerization for o MHI-a, o HHI-a, o HTI-a, and o PP-a centers at 258, 254, 252, and 234 °C, respectively, which were all lower than that of PH-a (a phenol- and aniline-based benzoxazine monomer) [33]. This suggests that the incorporation of the imide group into benzoxazine reduces the ring-opening polymerization temperature of the oxazine ring, e.g., through electro-withdrawal at the ortho -position of the oxazine ring.…”
Section: Resultsmentioning
confidence: 99%
“…During this curing process, the biophenol-based benzoxazine undergoes ring-opening polymerization followed by the formation of intermolecular hydrogen bonding of H–O…H and O–H…N molecules, as shown in Figure 3, which is a good agreement with the previous reports. 26 –29…”
Section: Methodsmentioning
confidence: 99%